FAMILY SIMULIIDAE - Wolff, Marta I.; Miranda-Esquivel, Daniel Rafael; Moncada-Alvarez, Ligia Ines (Zootaxa, 2016)
This catalogue presents 70 species distributed in two genera for Colombia: Gigantodax with 5 groups, and Simulium with 6 subgenera and 17 groups. Three species are recorded for the first time: Gigantodax vulcanius, G. gracilis, and Simulium pautense, and the distributional range is expanded to S.ochraceum, S. paynei, S. metallicum, and S. callidum.